2017
DOI: 10.3389/fevo.2017.00157
|View full text |Cite
|
Sign up to set email alerts
|

Secrets of Success in a Landscape of Fear: Urban Wild Boar Adjust Risk Perception and Tolerate Disturbance

Abstract: In urban areas with a high level of human disturbance, wildlife has to adjust its behavior to deal with the so called "landscape of fear." This can be studied in risk perception during movement in relation to specific habitat types, whereby individuals trade-off between foraging and disturbance. Due to its high behavioral plasticity and increasing occurrence in urban environments, wild boar (Sus scrofa) is an excellent model organism to study adjustment to urbanization. With the help of GPS tracking, space use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 80 publications
3
61
0
Order By: Relevance
“…Movement constraints imposed by human activity could be even more relevant for rural foxes that are less accustomed to human presence (see also Stillfried, Gras, et al, ). Our results show that rural foxes, unlike their city relatives, do not use artificial structures as dispersal corridors and that dispersal was limited by the city border (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Movement constraints imposed by human activity could be even more relevant for rural foxes that are less accustomed to human presence (see also Stillfried, Gras, et al, ). Our results show that rural foxes, unlike their city relatives, do not use artificial structures as dispersal corridors and that dispersal was limited by the city border (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been shown that wild boar show substantial plasticity regarding adjustment to human-dominated environments i.e. landscape of fear (Stillfried et al 2017); wild boar tolerate human presence by modulating their risk perception and even use humanassociated habitat classes. Wild boar dispersal is thus not limited by human-dominated environments and they may not experience a negative effect of habitat fragmentation during expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, these relationships have been assessed at the home-range scale [15]. However, more recent use of GPS collars provides the opportunity to assess movement paths and fine-scale movement behaviors within the home range [16,17,18]. To identify the direct impacts of foraging activities at perhaps the finest behavioral scale, it is necessary to analyze dietary preferences [19].…”
Section: Introductionmentioning
confidence: 99%